TLR8 ligation induces apoptosis of monocytic myeloid‐derived suppressor cells. Issue 1 (14th December 2017) - Dang, Yushe; Rutnam, Zina J.; Dietsch, Gregory; Lu, Hailing; Yang, Yi; Hershberg, Robert; Disis, Mary L.
Abstract: Myeloid‐derived suppressor cells (MDSCs) accumulate in tumors and the peripheral blood of cancer patients and demonstrate cancer‐promoting activity across multiple tumor types. A limited number of agents are known to impact MDSC activity. TLR8 is expressed in myeloid cells. We investigated expression of TLR8 on MDSC and the effect of a TLR8 agonist, motolimod, on MDSC survival and function. TLR8 was highly expressed in monocytic MDSC (mMDSC) but absent in granulocytic MDSC (gMDSC). Treatment of human PBMC with motolimod reduced the levels of mMDSC in volunteers and cancer donors versus control ( P < 0.001). Motolimod did not impact levels of gMDSC. The reduction of mMDSC was due to induced cell death by TLR8 ligation. Pretreatment of PBMC with a FAS neutralizing antibody inhibited motolimod‐induced reduction of mMDSC ( P < 0.001). Finally, we demonstrated that mMDSC impeded IL‐2 secretion by CD3/CD28‐activated T cells; IL‐2 secretion was partially restored when cells were cocultured with motolimod (142 ± 36 pg/ml vs. 59 ± 13 pg/ml; P = 0.03). There is increasing evidence that MDSCs contribute to the progression of cancer by inhibiting tumor‐directed T cells. TLR8 agonists may synergize with cancer immunotherapeutic approaches to enhance the antitumor effects of the adaptive immune response.